(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Currently, no industry can be imagined without digital technologies. Digitization plays an important role in our evolving lives. We can’t even imagine our daily lives without digital technologies. As a result of the digitization process, great changes have taken place in human life. We use in our daily lives transactions such as remote payments, online loan processing, which previously seemed to be impossible. Digitalization of the banking system is one of the key factors of development. This article discusses the advantages of using digitalization in the banking system and some drawbacks of this are also explained below.